Review of the genus Mesosaimia Breuning with description of a new species (Coleoptera: Cerambycidae: Lamiinae: Mesosini) - Yamasako, Junsuke (Zootaxa, 2014)
The genus Mesosaimia Breuning, 1938 is reviewed. The genus Trichipocregyes Breuning, 1950 is synonymized with Mesosaimia. Trichomesosa similis Breuning, 1950 is transferred to Mesosaimia. A new species, M. wakaharai sp. nov., is described from Laos. Four species, M. robusta Breuning, 1938, M. mausoni (Breuning, 1950) comb. nov., M. similis (Breuning) comb. nov. and M. wakaharai sp. nov., are included in the genus. Habitus photographs, drawings of diagnostic male genitalia, and a key to all species of Mesosaimia are provided.